PEMODELAN PEMBELAJARAN JARAK JAUH BERBASIS E-LEARNING DI UPN "VETERAN" JAKARTA DENGAN PENDEKATAN ENTERPRISE APPLICATION INTEGRATION - Tyanandarifah Rabiula (2021)
The development of information technology is very rapid and affects all aspects of life, including the field of education, one of which is the E-Learning-based Distance Learning (DL) process. It is important to standardize and optimize the available resources when using E-Learning in the distance learning process. It is important to incorporate E-learning systems and Academic Information Systems related to course data. Enterprise Application Integration (EAI) is a mechanism for integrating multiple applications without any modifications to the relevant applications, so that performance can be achieved in business operations. At Universitas Pembangunan Nasional "Veteran" Jakarta, EAI modeling on E-Learning-based distance learning will boost the efficacy of the learning process. It is expected to be able to refine the distance learning system based on E-Learning by applying the integration model.